LIFESTYLE IN SCHOOL CHILDREN OF ANÁPOLIS-GO. (Fiep Bulletin - online, 2013)
The aim of the study was to identify the lifestyle of students 10 to 12 years old from the city of Anapolis-GO. The sample was drawn in a stratified form, in 02 public schools, with a sample of 247 male children and 254 female children, making it a total 501 students. A modified lifestyle questionnaire was applied (Barros, NAHAS, 2003) to evaluate the style and life (free time spent by children when they were not in school, as well as the level of physical activity and eating habits). The results for the eating habits 81.8% male and 81.5% female are with considerable insufficient eating. For the physical activity level 23.5% male students and 26.4% of males as inactive, 23.1% and 27.2% are insufficiently active, 25.5% and 24.4% are moderately active; whereas 27.9% and 22.0% are active. The records showed that most students spend most of their free time watching television. The study concluded that the school children, regarding the level of physical activity, the male students are more active than females, and they both spend much of their free time watching television. Given the findings regarding eating habits, it can be concluded that both the male and female students adopt irregular eating habits in relation to what is suggested by the new food pyramid.
Keywords: lifestyle; eating habits; physical activity